Spatial evolution of an AMD stream in the Iberian Pyrite Belt: process characterization and control factors on the hydrochemistry - Grande, J. A. (2016)
This paper presents hydrochemical data of an AMD stream in the Iberian Pyrite Belt, obtained from its source, in the Poderosa Mine Portal, till its confluence at the Odiel River. The main objective is to establish potential interdependent relations between sulfate and metals’ loads and the following physical-chemical variables: pH, electric conductivity (EC), redox potential (EH), and dissolved oxygen (O2). All the parameters show a global increasing tendency since the tunnel’s exit to the confluence at Odiel River. The TDS and EC are two relevant exceptions. They behave similarly, showing a decreasing trend and a strong inflection that describes a minimum immediately after the discharging point. The spatial analysis combined with statistical tools put in evidence the typical AMD processes and the respective physical-chemical implications. Inputs with distinctive hydrochemical signatures impose relevant modifications in the Poderosa creek waters. This indicates low hydrochemical inertia and high vulnerability to external stimulus.